Pembalakan Liar (Studi Tentang Pola Jaringan Pembalakan Liar di Taman Nasional Bukit Barisan Selatan (TNBBS) Kabupaten Lampung Barat) - Elvira Elvira (Jurnal Kriminologi Indonesia, 2012)
Generally, the definition of illegal logging is all activity of logging, purchasing, or log trading without legal permission. Practically, illegal logging is conducted by logging in the area where it basically is prohibited to do such activity, but it becomes legal and perceives as collusion under the permission of local Official Illegal logging is illicitly committed by a criminal network the method used in this research is qualitative. Unstructured interviews and literature studies are used to complete the data. The result of this research shows that despite of the regulation pertaining to illegal logging activity, practically, the illegal activity still occurs in Indonesia with a certain pattern to avoid law administration. It is perceptible to conclude that illegal logging activity in Bukit Barisan Selatan National Park or Taman Nasional Bukit Barisan (TNBBS) is the embody of organized crime involving clandestine network that causes complicated law enforcement for such crime to prevail.